2000
DOI: 10.1017/s0954394500122033
|View full text |Cite
|
Sign up to set email alerts
|

Cross-dialectal comprehension as evidence for boundary mapping: Perceptions of the speech of southeastern Ohio

Abstract: Previous studies have shown that speakers have difficulty interpreting the sounds of another dialect when they are heard in isolation or reduced context, and that this difficulty is greater in areas of dialect contact where exposure to mergers or near-mergers is experienced (Labov & Ash, 1997; Labov, Karen, & Miller, 1991). A cross-dialectal comprehension test was conducted at Ohio University and three of its branch campuses. Responses were elicited to seven words digitally excerpted at three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…He found that Northerners and Southerners exhibited poorer intelligibility across regions than within regions in a standardized intelligibility test in noise. More recently, local dialect intelligibility benefits have been observed in phrase-final word recognition tests for listeners from Birmingham, Philadelphia, and Chicago (Labov and Ash 1997) and for listeners from different parts of Ohio (Flanigan and Norris 2000). In both studies, local listeners (from Birmingham and southern Ohio, respectively) more accurately identified the phrase-final target words than non-local listeners.…”
Section: Processing Benefits For the Local Varietymentioning
confidence: 94%
“…He found that Northerners and Southerners exhibited poorer intelligibility across regions than within regions in a standardized intelligibility test in noise. More recently, local dialect intelligibility benefits have been observed in phrase-final word recognition tests for listeners from Birmingham, Philadelphia, and Chicago (Labov and Ash 1997) and for listeners from different parts of Ohio (Flanigan and Norris 2000). In both studies, local listeners (from Birmingham and southern Ohio, respectively) more accurately identified the phrase-final target words than non-local listeners.…”
Section: Processing Benefits For the Local Varietymentioning
confidence: 94%
“…The past twenty years have witnessed much debate over the status of the Midland dialect area and its linguistic components (e.g., C. -J. N. Bailey 1968;Carver 1987;Davis & Houck 1992, 1996Frazer 1993Frazer , 1994Frazer , 1996Johnson 1994;McElhinny 1999;Flanigan & Norris 2000;Benson 2005;Murray & Simon 2006). The geographic patterns of use of want + prepositional adverb, both synchronically and diachronically, add to the dialogue.…”
Section: The Midland Dialect Areamentioning
confidence: 99%
“…The /u/~/υ/ merger before /l/ emanates from western Pennsylvania (Labov et al 2006:70;see Thomas 2001:51 for extensive citations). Researchers have also found it in Southern Ohio (Flanigan & Norris 2000). The pre-lateral liquid environment lowers the F 2 values for the preceding vowel, shrinking the formant space of the preceding vowel (Thomas 2001:50) and provides an opportunity for merger.…”
Section: Qualitative Assessment Of Phonological and Morphological Feamentioning
confidence: 99%